Low effective dispersal of asexual genotypes in heterogeneous landscapes by the endemic pathogen penicillium marneffei - Fisher M.C. (2014)
Long-distance dispersal in microbial eukaryotes has been shown to result in the establishment of populations on continental and global scales. Such "ubiquitous dispersal" has been claimed to be a general feature of microbial eukaryotes, homogenising populations over large scales. However, the unprecedented sampling of opportunistic infectious pathogens created by the global AIDS pandemic has revealed that a number of important species exhibit geographic endemicity despite long-distance migration via aerially dispersed spores. One mechanism that might tend to drive such endemicity in the face of aerial dispersal is the evolution of niche-adapted genotypes when sexual reproduction is rare. Dispersal of such asexual physiological "species" will be restricted when natural habitats are heterogeneous, as a consequence of reduced adaptive variation. Using the HIV-associated endemic fungus Penicillium marneffei as our model, we measured the distribution of genetic variation over a variety of spatial scales in two host species, humans and bamboo rats. Our results show that, despite widespread aerial dispersal, isolates of P. marneffei show extensive spatial genetic structure in both host species at local and country-wide scales. We show that the evolution of the P. marneffei genome is overwhelmingly clonal, and that this is perhaps the most asexual fungus yet found. We show that clusters of genotypes are specific to discrete ecological zones and argue that asexuality has led to the evolution of niche-adapted genotypes, and is driving endemicity, by reducing this pathogen's potential to diversify in nature. © 2005 Fisher et al.